2017
DOI: 10.1038/ctg.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Single Locoregional Triamcinolone Injection Immediately After Esophageal Endoscopic Submucosal Dissection Prevents Stricture Formation

Abstract: Objectives:Although endoscopic submucosal dissection (ESD) is an efficient treatment for superficial esophageal cancer, it is associated with stricture formation after wide-circumference resection that leads to a low quality of life. Although locoregional steroid injections prevent stricture formation, a randomized comparative study did not report any advantages associated with steroid injection. We evaluated the prophylactic efficacy of a single locoregional triamcinolone injection for stricture formation aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…First, this is the first study to investigate predictive factors for stricture formation in patients who received prophylactic locoregional triamcinolone injections after ESD. Stricture formation rate of patients who have received locoregional triamcinolone injections in the present study (16.8%) was similar to that of previous studies (10–20%) . A tumor circumferential extent >75% has been reported as a risk factor for refractory stricture development, which was defined as the requirement for more than three sessions of EBD to resolve the stricture, even in cases who have received locoregional triamcinolone injections .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…First, this is the first study to investigate predictive factors for stricture formation in patients who received prophylactic locoregional triamcinolone injections after ESD. Stricture formation rate of patients who have received locoregional triamcinolone injections in the present study (16.8%) was similar to that of previous studies (10–20%) . A tumor circumferential extent >75% has been reported as a risk factor for refractory stricture development, which was defined as the requirement for more than three sessions of EBD to resolve the stricture, even in cases who have received locoregional triamcinolone injections .…”
Section: Discussionsupporting
confidence: 89%
“…Locoregional steroid injections may prevent stricture formation after esophageal ESD . Giving locoregional corticosteroids may inhibit collagen synthesis, fibrosis, and inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Steroid therapy decreases stricture better than preventive EBD. 11 Efficacy of prophylactic steroid injection for post-ESD ulcer was reported in four observational studies [12][13][14][15] (Table 1). Most studies reported that steroid injection decreased the incidence of post-ESD stricture in high-risk patients, and one systematic review showed that injection steroid was superior to oral steroid in prevention of post-ESD stricture.…”
Section: Management Of Adverse Events Related To Esophageal Esdmentioning
confidence: 99%